A place for Miguel: discovering the power of belonging within an inclusive toddler community. Issue 1 (2nd January 2023) - Recchia, Susan L.; McDevitt, Seung Eun
ABSTRACT: In this phenomenological case study, we explore how a toddler with autism (Miguel) becomes a member of an early childhood learning community. Drawing on the right to belong and a social-relational model of disability framework, we asked research questions that are fundamental to the rights and agency of the child and how children experience inclusion and belonging in their learning community. By following Miguel during his first year in early care and education, we share depictions of his expressions of interest, initiations, and agency; his ways of relating to children and adults in the classroom; his use of environmental supports and scaffolds to engage with the physical and interpersonal space; and his growing sense of membership in the toddler classroom. In conclusion, we discuss what inclusion means to individual children and the ways in which inclusive practices can unfold in a setting that promotes authentic belonging.